The Effect of Blood Lactate Level on Mortality in COVID-19 Positive Patients - Yeşim İşler; Halil Kaya; Melih Yüksel; Mehmet Oğuzhan Ay; Şükrü İşler; Mehtap Bulut (Eurasian Journal of Emergency Medicine, 2021)

(untitled)
Aim:We aimed to investigate the relationship between increased lactate values and mortality in COVID-19 patients.Materials and Methods:This study was conducted in a tertiary training and research hospital. According to the order of application, a total of 316 patients over the age of 18 who were admitted to the emergency department (ED) with symptoms of COVID-19 during the two months and whose data could be completely accessed were included in the study retrospectively. Plasma lactate values and mortality within 28 days were determined.Results:The median age of the patients was 69 years. Of the patients, 53.5% were male, 72.2% had comorbidities, and the most common comorbidity was COPD (13.0%). Of the patients, 83.5% were hospitalized. The mean lactate value of the patients was 2.05 ± 1.45mmol / L. Mortality developed in 14.2% of the patients during the first 28 days. The 28-day mortality was significantly higher in patients with a positive Polymerase Chain Reaction (PCR) (23.8%) than that of negative PCR (8.2%) (p < 0.001). The lactate level was found to be significantly different in both PCR positive and negative groups in which mortality developed within 28 days (p < 0.001; p < 0.001). If the cut-off value of lactate in terms of mortality was 2.45, the sensitivity and specificity were determined as 80.0% and 81.2%, respectively.Conclusion:In patients with COVID-19 infection, the blood lactate level examined at the first admission to ED can be used as a practical screening test to predict mortality.